Impact of persistent barrier to gene flow and catastrophic events on red algae evolutionary history along the Chilean coast - Huanel, Oscar R.; Montecinos, Alejandro E.; Sepúlveda-Espinoza, Francisco; Guillemin, Marie-Laure (Frontiers in Genetics, 2024)
Historical vicariance events, linked to the existence of stable physical barriers to gene flow, generate concordant genetic breaks in co-distributed species while stochastic processes (e.g., costal uplift) Historical vicariance events, linked to the existence of stable physical barriers to gene flow, generate concordant genetic breaks in co-distributed species while stochastic processes (e.g., costal uplift) could cause species-specific genetic breaks as a result of local strong demographic bottlenecks or extinction. In Chile, previous studies show that the area of the 30°S-33°S could correspond to a stable barrier to gene flow that have affected the genetic structure of various algae and marine invertebrates. Here we sequenced two organellar genes (COI and rbcL) in four taxonomically accepted co-distributed red seaweeds species characterized by a low dispersal potential: Mazzaella laminarioides, M. membranacea, Asterfilopsis disciplinalis, and Ahnfeltiopsis vermicularis. Our results revealed the existence of ten strongly differentiated linages in the taxa studied. Strong genetic breaks, concordant in both space and time (divergence estimated to have occurred some 2.9-12.4 million years ago), were observed between taxa distributed across the 33°S. Conversely, in the Central/South part of the Chilean coast, the localization of the genetic breaks/sub-structure observed varied widely (36ºS, 38ºS, 39ºS, and 40ºS). These results suggest that a major historical vicariance event has modeled the genetic structure of several Chilean marine organisms in the north of the Chilean coast during the mid-Miocene, while more recent stochastic events and genetic drift could be the driving forces of genetic divergence/structuration in the central-southern part of the coast.